2023
DOI: 10.1158/1940-6207.c.6546995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from Stress-induced Norepinephrine Downregulates CCL2 in Macrophages to Suppress Tumor Growth in a Model of Malignant Melanoma

Abstract: <div>Abstract<p>Psychological stressors have been implicated in the progression of various tumor types. We investigated a role for stress in tumor immune cell chemotaxis in the B16F10 mouse model of malignant melanoma. We exposed female mice to 6-hour periods of restraint stress (RST) for 7 days, then implanted B16F10 malignant melanoma tumor cells and continued the RST paradigm for 14 additional days. We determined serum corticosterone and liver catecholamine concentrations in these mice. To evalu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…CCL2 is a major chemoattractant implicated in the infiltration of myeloid cells, especially monocytes and neutrophils, into the brain during inflammation 89,90 . A relationship between NE and CCL2 has not been extensively examined in microglia, but a recent report demonstrated that NE reduces CCL2 production in mouse and human macrophages in a β-adrenergic receptor-dependent manner 91 . Additionally, recent work in astrocytes has revealed a complicated relationship between NE and CCL2 that may provide insight for the data in this study and others.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 is a major chemoattractant implicated in the infiltration of myeloid cells, especially monocytes and neutrophils, into the brain during inflammation 89,90 . A relationship between NE and CCL2 has not been extensively examined in microglia, but a recent report demonstrated that NE reduces CCL2 production in mouse and human macrophages in a β-adrenergic receptor-dependent manner 91 . Additionally, recent work in astrocytes has revealed a complicated relationship between NE and CCL2 that may provide insight for the data in this study and others.…”
Section: Discussionmentioning
confidence: 99%